Arts education and literacies - Jensen, Amy Petersen; Draper, Roni Jo. (New York : Routledge, 2015)
In a struggling global economy, education is focused on core subjects such as language arts and mathematics, and the development of technological and career-readiness skills. Arts education has not been a central focus of education reform movements in the United States, and none of the current education standards frameworks deeply address the processes, texts and literacies that are inherent to arts disciplines. This lack of clarity poses a problem for state and district leaders who might be inclined to advocate for the arts in schools and classrooms across the country, but cannot find adequate detail in their guiding frameworks.
Includes bibliographical references.
Keywords: Arts -- Study and teaching